European traded gas hubs: the markets have rebalanced - Patrick Heather (The Oxford Institute for Energy Studies, 2024)
European gas markets experienced a very turbulent period from 2020 to 2022, which led to the lowest ever northwest European gas prices at the end of May 2020, then several strong rallies led to four successive 'highest ever' prices, the most recent being in August 2022. After each of those rallies, markets retraced back down to around exteuro60/MWh. There was one last smaller but equally steep rally at the end of 2022, resulting in a high on 7th December 2022 when the THE closed at exteuro149.11/MWh. The focus of this paper is to review the European traded gas markets during 2023 to see whether they have remained uncertain, volatile and have the potential to revisit those highs or, by contrast, whether they can be said to have 'rebalanced' to any degree. The paper analyses the results of the author's 5 Key Elements, as well as the effect of large LNG imports, and five long term market trends (traded volumes development, Month Ahead prices and the spreads between hubs, price convergence, correlation and volatility). In 2023, trading picked up significantly, set against a general fall in physical volumes. When comparing the 2022/23 year on year difference, Europe as a whole had a 40% rise in traded volumes, whilst physical demand fell by -18%. All countries had higher traded volumes except Belgium, Great Britain and Romania and all had lower physical demand, except Bulgaria, Denmark and Romania. Having examined each of the 5 Key Elements in detail, as well as several complimentary analyses, it is clear that the Dutch TTF is far and away the leading European traded gas hub, used by many more market participants than any other hub, has a very high traded products score, with far greater total traded volumes than all the others put together. TTF also accounts for 81.5% of all European gas trading, for 56% of all OTC trading, and 87% of all exchange trading. TTF also has the highest Tradability Index score, only missing one point on one of the 'balance of month' contracts, and finally, by far the greatest churn rate. The author's 2022 paper concluded that there was indeed an 'LNG effect' on traded volumes in those countries that imported large additional cargoes of LNG. This was borne out in 2023 also as there was a large increase in traded volumes and churn rate at the Dutch TTF and the Netherlands was the only country with an increase in LNG sendout in 2023 compared to 2022. The actual correlation coefficients of some of the main 'pairs' of hubs show near perfect correlation of the three large NWE LNG importers to the benchmark TTF before and since the extraordinary market conditions in 2022. Month Ahead spreads are commonly traded in the European gas markets, principally because it is the MA contract that is most used in pricing underlying physical contracts and therefore, it is the MA contracts, OTC and especially exchange futures, that are most used in the risk management of physical gas portfolios. The graphs in this paper show that it was the French TRF versus Dutch TTF spread that recorded the highest differential during the turbulent trading period of 2022, but the other main European hubs also saw wide variations in their basis prices to TTF. The TTF/TRF spread has over time been marginally negative but in 2022 went positive due to the large quantities of LNG imported into France; however, from early October 2022 the TTF premium fell quite sharply, and even went a touch negative in early January 2023, before stabilising over the course of the year. Although there was a brief small increase in Q4-2023, it fell back again in early 2024. The volatility graph for the benchmark TTF alone from 2007 to 2023 shows that during the most extreme 13 months from Q4-2021 to Q4-2022, both in terms of extremely high absolute levels and steep rises and sharp dips, average volatility was 137.36%. This dropped sharply and in December 2023 average volatility was 73.75%. For now at least it appears that to a large extent the TTF market has also rebalanced in terms of volatility. NBP aside, volatility at the continental hubs was always highest at the French TRF, whereas the TTF had the lowest volatility in H2-2021 and was middling in both 2022 and 2023, when VTP was lowest. Not only was the TRF the most volatile market on average throughout the turbulent period from H2-2021 through 2022 and into early 2023 but it appears to have remained so in the latter part of 2023 as well. The final conclusion of this paper is that the trading at TTF has rebalanced and indeed, gone from strength to strength. The other European hubs can also be said to have rebalanced on the whole, with some exceptions, particularly at some emerging hubs. With regards to the analyses on long term trends, price spreads, price correlation and price volatilities they also show to a large degree that the markets have rebalanced. Finally, Henry Hub and JKM trading has also rebounded.
Keywords: 330; European (traded) gas hubs; Gas benchmarks; Gas markets have rebounded; Gas price benchmarks; Global churn rates; Global gas benchmarks; TTF European gas Benchmark; TTF has rebalanced; TTF leading European gas hub